(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: A penetrating ocular injury with limbal involvement leads to limbal stem cell deficiency and poor corneal regeneration. Purpose: To assess treatment outcomes of primary surgical repair (PSR) involving autolimbal grafting versus conventional PSR in penetrating ocular injuries with limbal involvement. Materials and Methods: Patients were retrospectively divided into two groups comparable in age, type of trauma and time from injury to admittance. Group 1 comprised 26 patients (26 eyes) who had PSR with autolimbal grafting, while Group 2 (the control group) comprised 24 patients (24 eyes) who had conventional PSR for penetrating ocular injuries with limbal involvement. Wound margin state, scar formation period, regression of inflammatory response, and presence of vascularized scar were used as outcome measures. Results: After treatment, the number of eyes with visual acuity of 0.1 or better was 19 (73.08%; including 12 eyes (46.2±6.5%) with visual acuity of 0.7 to 0.9) in Group 1 versus 5 (20.8±6.6%) in the control group. Conclusion: The proposed technique of PSR with autolimbal grafting for penetrating injuries with limbal involvement demonstrated advanced correction for wound margin adaptation and resulted in faster wound regeneration.